SLOW THINKING, OR THE ART OF NETWORK THINKING - Piekarczyk, Anna; Strojny, Szymon (Management and Administration Journal, 2024)
This article presents Slow Thinking: a reason and action tool used in problem-solving, also referred to as the methodology of network thinking. This methodology allows us to better understand the working of systems, specifically complex systems. It provides a holistic approach, a broad outlook, and examination of the world and a discovering of new relations; all this requires holistic thinking. Here attention is also drawn to the pitfalls of fast thinking and the need to develop the competence of slow thinking. The authors also present exemplary applications of slow thinking with a network model that demonstrates the impact of demographic changes and globalisation on the development of Europe.